Playing for their nation : baseball and the American military during World War II - Bullock, Steven R. (Book collections on Project MUSE., 2004)
Just two months after the magical baseball season of 1941, the United States entered World War II, and baseball, like other American institutions, was called upon to sacrifice and serve in the war effort. Utilizing personal accounts, military documents, and newspaper sources, Playing for Their Nation provides the first in-depth analysis of the development of military baseball during the Second World War.